Inflamed and unrewarded: a narrative review exploring neuroinflammation and its impact on the brain’s reward mechanisms - Sharma, Saksham; Kaur, Harsimar; Kumar, Akshaya J.; Gandhi, Dhruv; Malhotra, Vani; Srinivasan, Sahana; Reddy, Puneeth (International Journal of Research in Medical Sciences, 2025)
Depression is associated with dysfunction in the brain’s reward system, contributing to symptoms like anhedonia. Emerging evidence suggests that neuroinflammation plays a key role in disrupting dopaminergic pathways. This review explores how pro-inflammatory cytokines affect reward circuitry and assesses the potential of anti-inflammatory treatments. A narrative review was conducted using studies from 2000 to 2025. Databases searched included PubMed and Google Scholar. Keywords focused on depression, neuroinflammation, reward systems, cytokines, and treatment strategies. Studies in adults examining neural and behavioural outcomes were included. Pro-inflammatory cytokines (e.g., IL-6, TNF-α) impair dopamine function and alter connectivity in the mesolimbic pathway. These changes are linked to core depressive symptoms. Anti-inflammatory agents—such as TNF inhibitors, NSAIDs, and probiotics—have shown promise in alleviating symptoms, particularly in patients with high inflammation. Neuroinflammation plays a critical role in the pathophysiology of depression through its detrimental impact on dopaminergic reward pathways. Targeting inflammation presents a promising strategy for treating depression, particularly subtypes characterised by elevated immune activation. Future research should aim for biomarker-driven stratification to optimise individualised therapeutic approaches.